Paradigmatic Relationships In The Dictionary Of "Hibatul Haqaiq" - Sindorov Lutfulla Kurolovich (Genius Publishing Group, 2022)
In the article, the lexical-semantic relations in the dictionary of the epic "Hibatulhaqayiq" are based on the general laws of lexical development, as well as homonymous lexemes, synonymous lines, antonymous lines, as well as other memorable lexicons. paradigmatic relationships related to affixal antonyms are highlighted.
Keywords: Ahmad Yugnak; Hibatul Haqiq; vocabulary; homonymy